Uporaba veččutnega poučevanja pri pouku tujih jezikov - Šepec, Vanja (Vestnik za tuje jezike, 2013)
Multi sensory teaching techniques stimulate learning by engaging students on multiple levels and help them to learn a new language through using a variety of senses.Those techniques are hardly ever used in Slovenian school system and the below article focuses on presenting the latest findings in regards to benefits that sensory perception can have in learning processes. The article also outlines useful tools and various sensory and perception classroom activities used in teaching French as a second language.
Keywords: francoščina; French; tuji jeziki; jezikovni pouk; veččutno poučevanje; VAKOG; zaznavni sistemi; tipi osebnosti